Anti-corrosion process for screw of screw vacuum pump

Through a multi -step anti -corrosion process, including sandblasting, alkaline washing, electrical abandonment and other steps, a uniform anticorrosive layer is formed, which solves the problem of easy corrosion of the screw vacuum pump, significantly extend the life of the equipment and improves wear resistance and corrosion resistance.

CN119372584AInactive Publication Date: 2025-01-28GUANGDE DIWEI VACUUM EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411283246.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing screw vacuum pumps are susceptible to corrosion during use, resulting in a shortening of the equipment life and cannot meet the requirements of cleaning, oil-free and corrosion-resistant.

Method used

A kind of anti -corrosion process, including sandblasting, alkaline washing, electrical abandonment, ultrasonic cleaning, drying, nitrogen seepage, heating dust treatment, etc., to form a uniform anti -corrosion layer to improve the wear resistance and corrosion resistance of the equipment.

Benefits of technology

This process can significantly extend the service life of the vacuum pump of the screw, improve the wear resistance and corrosion resistance of the equipment, the performance is better than the current organic coating, and has good uniformity, smoothness, adhesion and corrosion capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372584A_ABST
    Figure CN119372584A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-corrosion process for a screw of a screw vacuum pump, and relates to the technical field. The method comprises the following steps that S1, sand blasting is conducted, specifically, a refined quartz sand grinding material is subjected to sand blasting on the surface of the screw of the screw vacuum pump through a sand blasting gun, and the particle size of the refined quartz sand grinding material is 0.1-0.3 MM; and S2, alkali washing is conducted, specifically, the workpiece is soaked in high-strength alkali liquor in an electrolyte tank for 6-8 h. And S3, electric degreasing is conducted, specifically, the temperature is increased to 40-50 DEG C after alkali washing, and direct current with the density being 3-5 A / dm < 2 > is introduced to the workpiece. And S4, cleaning is conducted, specifically, the workpiece is placed in an ultrasonic cleaning machine to be subjected to ultrasonic cleaning operation. And S5, drying is conducted, specifically, the workpiece is put into a hot air dryer and is blow-dried with hot air. And S6, nitriding: nitriding is carried out in a JT-25 type gas nitriding furnace. And S7, heating dust treatment is conducted, specifically, the workpiece is heated and smeared. And S8, cooling. The process can improve the wear resistance and corrosion resistance of the equipment, prolongs the service life of the equipment by more than 3 times, has the performance superior to that of the currently used organic paint, and is suitable for different substrates such as carbon steel, cast iron and nonferrous metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of screw anti-corrosion treatment, and in particular relates to an anti-corrosion process for a screw of a screw vacuum pump. Background Art

[0002] The screw vacuum pump is an exhaust device that uses a pair of screws to rotate synchronously at high speed in opposite directions in the pump casing to produce suction and exhaust effects. It is an upgraded version of the oil-sealed vacuum pump and can extract gases containing a large amount of water vapor and a small amount of dust. It is widely used in domestic pharmaceutical, chemical, semiconductor and other corporate fields that have high requirements for clean vacuum.

[0003] The two screws are finely balanced, supported by bearings, and installed in the pump housing. There is a certain gap between the screws, so when the pump is working, there is no friction between them, the operation is stable, the noise is low, and no lubricating oil is required in the working chamber. Therefore, the dry screw pump can extract gas containing a large amount of water vapor and a small amount of dust, with higher ultimate vacuum, lower power consumption, energy saving, maintenance-free, etc. It is an updated product of the oil-sealed vacuum pump.

[0004] The development of various vacuum pumps is increasingly affected by vacuum application scenarios. General vacuum systems cannot meet the requirements of cleanliness, oil-freeness and corrosion resistance. Since screw pumps pump gases containing a large amount of water vapor and a small amount of dust, the screw surface needs to be treated with anti-corrosion during the production process to ensure the service life of the screw vacuum pump. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-corrosion process for the screw of a screw vacuum pump, which solves the existing problems

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] The present invention is an anti-corrosion process for a screw of a screw vacuum pump, comprising the following steps:

[0008] S1. Sandblasting: Use a sandblasting gun to blast the refined quartz sand abrasive on the screw surface of the screw vacuum pump. The refined quartz sand abrasive has a particle size of 0.1-0.3MM.

[0009] S2. Alkali washing: Soak the workpiece in high-strength alkaline solution in the electrolyte tank for 6H-8H.

[0010] S3. Electrodegreasing: After alkaline washing, the temperature is heated to 40℃~50℃, and a direct current with a current density of 3A / dm2~5A / dm2 is passed through the workpiece.

[0011] S4. Cleaning: Place the workpiece in an ultrasonic cleaning machine for ultrasonic cleaning, using a working temperature of 30-40KHz and 50℃-70℃.

[0012] S5. Drying: Put the workpiece into the hot air dryer and dry it with hot air.

[0013] S6. Nitriding: It is carried out in a JT-25 gas nitriding furnace, using ammonia and ethanol as nitriding agents and MgCl2 as a catalyst.

[0014] S7, Heating Dust Treatment: Heat and apply to the workpiece.

[0015] S8. Cooling.

[0016] Furthermore, in S3, the cathode is electrolyzed for 1 to 2 minutes, and the anode is electrolyzed for 10 to 20 seconds.

[0017] Furthermore, the process of S6 includes:

[0018] (1) Place the workpiece in a gas nitriding furnace and seal the gas nitriding furnace.

[0019] (2) The temperature in the gas nitriding furnace is set at 570°C-600°C and heated for 4 hours.

[0020] (3) After the treatment is completed, turn off the ethanol and continue to pass ammonia at 100L / h to maintain a positive pressure of 400-500KPa in the furnace.

[0021] (4) After infiltration, air cool the mixture after it is taken out of the furnace.

[0022] Furthermore, the heating and applying step in S7 includes:

[0023] (1) First heating: Place the workpiece in a hot oven and heat it at 300°C for more than 40 minutes.

[0024] (2) First powder coating: flame temperature: 1800°C, flame speed: 1000m / s, powder feeding speed: 100-150g / min, powder feeding gas flow: 600-800L / h

[0025] (3) Secondary heating: Place the workpiece in a hot oven and heat it at 500°C for more than 40 minutes

[0026] (4) Secondary powder coating: flame temperature: 2000°C, flame speed: 1500m / s.

[0027] Furthermore, the amount of ammonia passed in (2) is 500 L / h, and the amount of anhydrous ethanol is 50 L / min.

[0028] Furthermore, in said (4), the powder feeding speed is 80-100 g / min, and the powder feeding gas flow rate is 400-600 L / h.

[0029] The present invention has the following beneficial effects:

[0030] This process can improve the wear resistance and corrosion resistance of equipment and extend its service life by more than 3 times. Its performance is better than the organic coating currently used, and it is suitable for different substrates such as carbon steel, cast iron, non-ferrous metals, etc. Through this process, it has good uniformity and can obtain a uniform anti-corrosion layer on any complex parts. It is an amorphous uniform single-phase structure, without grain boundary dislocation, chemical component segregation, high finish, and excellent adhesion, providing an ideal barrier layer for corrosion prevention. It has corrosion resistance in alkali, salt, high temperature, organic medium solvent, and acidic gas. It has been proved by practical application that it has good corrosion resistance to Cl-ion stress corrosion, high and low temperature H2S and cyclopentane acid corrosion. At the same time, it also has the characteristics of high temperature resistance, anti-adhesion, electrical insulation and anti-static. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1 The present invention is a flow chart of the anti-corrosion process of the screw of the screw vacuum pump. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0034] Embodiment 1:

[0035] An anti-corrosion process for a screw of a screw vacuum pump comprises the following steps:

[0036] S1. Sandblasting: Use a sandblasting gun to blast the refined quartz sand abrasive on the screw surface of the screw vacuum pump. The refined quartz sand abrasive has a particle size of 0.1-0.3MM.

[0037] S2. Alkali washing: Soak the workpiece in high-strength alkaline solution in the electrolyte tank for 6H-8H.

[0038] S3. Electro-degreasing: After alkaline washing, the temperature is heated to 42°C and a direct current with a current density of 3A / dm2 to 5A / dm2 is passed through the workpiece.

[0039] S4. Cleaning: Place the workpiece in an ultrasonic cleaning machine for ultrasonic cleaning, using a working temperature of 30-40KHz and 55°C.

[0040] S5. Drying: Put the workpiece into the hot air dryer and dry it with hot air.

[0041] S6. Nitriding: It is carried out in a JT-25 gas nitriding furnace, using ammonia and ethanol as nitriding agents and MgCl2 as a catalyst.

[0042] S7, Heating Dust Treatment: Heat and apply to the workpiece.

[0043] S8. Cooling.

[0044] In S3, the cathode is electrolyzed for 1 minute, and the anode is electrolyzed for 10 seconds.

[0045] The process of S6 includes:

[0046] (1) Place the workpiece in a gas nitriding furnace and seal the gas nitriding furnace.

[0047] (2) The temperature in the gas nitriding furnace is set to 570°C and heated for 4 hours.

[0048] (3) After the treatment is completed, turn off the ethanol and continue to pass ammonia at 100L / h to maintain a positive pressure of 400-500KPa in the furnace.

[0049] (4) After infiltration, air cool the mixture after it is taken out of the furnace.

[0050] The heating and applying step in S7 includes:

[0051] (1) First heating: Place the workpiece in a hot oven and heat it at 300°C for more than 40 minutes.

[0052] (2) First powder coating: flame temperature: 1800°C, flame speed: 1000m / s, powder feeding speed: 100-150g / min, powder feeding gas flow: 600-800L / h

[0053] (3) Secondary heating: Place the workpiece in a hot oven and heat it at 500°C for more than 40 minutes

[0054] (4) Secondary powder coating: flame temperature: 2000°C, flame speed: 1500m / s.

[0055] The amount of ammonia passed in (2) is 500 L / h, and the amount of anhydrous ethanol is 50 L / min.

[0056] In the step (4), the powder feeding speed is 80-100 g / min, and the powder feeding gas flow rate is 400-600 L / h.

[0057] Embodiment 2:

[0058] The following steps are involved:

[0059] S1. Sandblasting: Use a sandblasting gun to blast the refined quartz sand abrasive on the screw surface of the screw vacuum pump. The refined quartz sand abrasive has a particle size of 0.1-0.3MM.

[0060] S2. Alkali washing: Soak the workpiece in high-strength alkaline solution in the electrolyte tank for 6H-8H.

[0061] S3. Electro-degreasing: After alkaline washing, the temperature is heated to 45°C and a direct current with a current density of 3A / dm2 to 5A / dm2 is passed through the workpiece.

[0062] S4. Cleaning: Place the workpiece in an ultrasonic cleaning machine for ultrasonic cleaning, using a working temperature of 30-40KHz and 60°C.

[0063] S5. Drying: Put the workpiece into the hot air dryer and dry it with hot air.

[0064] S6. Nitriding: It is carried out in a JT-25 gas nitriding furnace, using ammonia and ethanol as nitriding agents and MgCl2 as a catalyst.

[0065] S7, Heating Dust Treatment: Heat and apply to the workpiece.

[0066] S8. Cooling.

[0067] In the S3, the cathode is electrolyzed for 1.5 minutes, and the anode is electrolyzed for 15 seconds.

[0068] The process of S6 includes:

[0069] (1) Place the workpiece in a gas nitriding furnace and seal the gas nitriding furnace.

[0070] (2) The temperature in the gas nitriding furnace is set to 570°C and heated for 4 hours.

[0071] (3) After the treatment is completed, turn off the ethanol and continue to pass ammonia at 100L / h to maintain a positive pressure of 400-500KPa in the furnace.

[0072] (4) After infiltration, air cool the product after it is taken out of the furnace.

[0073] The heating and applying step in S7 includes:

[0074] (1) First heating: Place the workpiece in a hot oven and heat it at 300°C for more than 40 minutes.

[0075] (2) First powder coating: flame temperature: 1800°C, flame speed: 1000m / s, powder feeding speed: 100-150g / min, powder feeding gas flow: 600-800L / h

[0076] (3) Secondary heating: Place the workpiece in a hot oven and heat it at 500°C for more than 40 minutes

[0077] (4) Secondary powder coating: flame temperature: 2000°C, flame speed: 1500m / s.

[0078] The amount of ammonia passed in (2) is 500 L / h, and the amount of anhydrous ethanol is 50 L / min.

[0079] In the step (4), the powder feeding speed is 80-100 g / min, and the powder feeding gas flow rate is 400-600 L / h.

[0080] Embodiment three:

[0081] The following steps are involved:

[0082] S1. Sandblasting: Use a sandblasting gun to blast the refined quartz sand abrasive on the screw surface of the screw vacuum pump. The refined quartz sand abrasive has a particle size of 0.1-0.3MM.

[0083] S2. Alkali washing: Soak the workpiece in high-strength alkaline solution in the electrolyte tank for 6H-8H.

[0084] S3. Electrodegreasing: After alkaline washing, the temperature is heated to 47°C and a direct current with a current density of 3A / dm2 to 5A / dm2 is passed through the workpiece.

[0085] S4. Cleaning: Place the workpiece in an ultrasonic cleaning machine for ultrasonic cleaning, using a working temperature of 30-40KHz and 65°C.

[0086] S5. Drying: Put the workpiece into the hot air dryer and dry it with hot air.

[0087] S6. Nitriding: It is carried out in a JT-25 gas nitriding furnace, using ammonia and ethanol as nitriding agents and MgCl2 as a catalyst.

[0088] S7, Heating Dust Treatment: Heat and apply to the workpiece.

[0089] S8. Cooling.

[0090] In the S3, the cathode is electrolyzed for 2 minutes, and then the anode is electrolyzed for 20 seconds.

[0091] The process of S6 includes:

[0092] (1) Place the workpiece in a gas nitriding furnace and seal the gas nitriding furnace.

[0093] (2) The temperature in the gas nitriding furnace is set to 580°C and heated for 4 hours.

[0094] (3) After the treatment is completed, turn off the ethanol and continue to pass ammonia at 100L / h to maintain a positive pressure of 400-500KPa in the furnace.

[0095] (4) After infiltration, air cool the product after it is taken out of the furnace.

[0096] The heating and applying step in S7 includes:

[0097] (1) First heating: Place the workpiece in a hot oven and heat it at 300°C for more than 40 minutes.

[0098] (2) First powder coating: flame temperature: 1800°C, flame speed: 1000m / s, powder feeding speed: 100-150g / min, powder feeding gas flow: 600-800L / h

[0099] (3) Secondary heating: Place the workpiece in a hot oven and heat it at 500°C for more than 40 minutes

[0100] (4) Secondary powder coating: flame temperature: 2000°C, flame speed: 1500m / s.

[0101] The amount of ammonia passed in (2) is 500 L / h, and the amount of anhydrous ethanol is 50 L / min.

[0102] In the step (4), the powder feeding speed is 80-100 g / min, and the powder feeding gas flow rate is 400-600 L / h.

[0103] Embodiment 4:

[0104] The following steps are involved:

[0105] S1. Sandblasting: Use a sandblasting gun to blast the refined quartz sand abrasive on the screw surface of the screw vacuum pump. The refined quartz sand abrasive has a particle size of 0.1-0.3MM.

[0106] S2. Alkali washing: Soak the workpiece in high-strength alkaline solution in the electrolyte tank for 6H-8H.

[0107] S3. Electrodegreasing: After alkaline washing, the temperature is heated to 50°C and a direct current with a current density of 3A / dm2 to 5A / dm2 is passed through the workpiece.

[0108] S4. Cleaning: Place the workpiece in an ultrasonic cleaning machine for ultrasonic cleaning, using a working temperature of 30-40KHz and 70°C.

[0109] S5. Drying: Put the workpiece into the hot air dryer and dry it with hot air.

[0110] S6. Nitriding: It is carried out in a JT-25 gas nitriding furnace, using ammonia and ethanol as nitriding agents and MgCl2 as a catalyst.

[0111] S7, Heating Dust Treatment: Heat and apply to the workpiece.

[0112] S8. Cooling.

[0113] In S3, the cathode is electrolyzed for 2 minutes, and the anode is electrolyzed for 20 seconds.

[0114] The process of S6 includes:

[0115] (1) Place the workpiece in a gas nitriding furnace and seal the gas nitriding furnace.

[0116] (2) The temperature in the gas nitriding furnace is set to 590°C and heated for 4 hours.

[0117] (3) After the treatment is completed, turn off the ethanol and continue to pass ammonia at 100L / h to maintain a positive pressure of 400-500KPa in the furnace.

[0118] (4) After infiltration, air cool the mixture after it is taken out of the furnace.

[0119] The heating and applying step in S7 includes:

[0120] (1) First heating: Place the workpiece in a hot oven and heat it at 300°C for more than 40 minutes.

[0121] (2) First powder coating: flame temperature: 1800°C, flame speed: 1000m / s, powder feeding speed: 100-150g / min, powder feeding gas flow: 600-800L / h

[0122] (3) Secondary heating: Place the workpiece in a hot oven and heat it at 500°C for more than 40 minutes

[0123] (4) Secondary powder coating: flame temperature: 2000°C, flame speed: 1500m / s.

[0124] The amount of ammonia passed in (2) is 500 L / h, and the amount of anhydrous ethanol is 50 L / min.

[0125] In the step (4), the powder feeding speed is 80-100 g / min, and the powder feeding gas flow rate is 400-600 L / h.

[0126] The principle and effect of the present invention are: an anti-corrosion process for the screw of a screw vacuum pump, which can improve the wear resistance and corrosion resistance of the equipment, extend its service life by more than 3 times, and has better performance than the currently used organic coatings, and is suitable for different substrates such as carbon steel, cast iron, non-ferrous metals, etc. Through the process, it has good uniformity, and a uniform anti-corrosion layer is obtained on parts with any complex shapes. It is an amorphous uniform single-phase structure, there is no grain boundary dislocation, no chemical component segregation, and it also has a high degree of finish and excellent adhesion, providing an ideal barrier layer for corrosion prevention, and has corrosion resistance in alkali, salt, high temperature, organic medium solvents, and acidic gases. It has been proved by practical application that it has good corrosion resistance to Cl-ion stress corrosion, high and low temperature H2S and cyclopentane acid corrosion.

[0127] It also has:

[0128] (1) High temperature resistance: can be used for a long time at temperatures of -40 to 300°C.

[0129] (2) Anti-stickiness: Almost all substances cannot adhere to it, making it anti-stick and easy to clean.

[0130] (3) Electrical insulation: It has excellent insulation resistance performance, and its electrical insulation is not affected by temperature.

[0131] (4) Anti-static: Because the coating has strong toughness and tensile strength after film formation, it is almost impossible to generate static electricity on the surface, making it suitable for flammable and explosive occasions.

[0132] The above are only preferred embodiments of the present invention and do not limit the present invention. Any modification to the technical solutions recorded in the aforementioned embodiments, any equivalent replacement of some of the technical features therein, and any modification, equivalent replacement, and improvement made are all within the protection scope of the present invention.

Claims

1. A corrosion protection process for a screw vacuum pump screw, characterized in that: The following steps are involved: S1. Sandblasting: Use a sandblasting gun to blast the refined quartz sand abrasive on the screw surface of the screw vacuum pump. The refined quartz sand abrasive has a particle size of 0.1-0.3MM. S2. Alkali washing: Soak the workpiece in high-strength alkaline solution in the electrolyte tank for 6H-8H. S3. Electrodegreasing: After alkaline washing, the temperature is heated to 40℃~50℃, and a direct current with a current density of 3A / dm2~5A / dm2 is passed through the workpiece. S4. Cleaning: Place the workpiece in an ultrasonic cleaning machine for ultrasonic cleaning, using a working temperature of 30-40KHz and 50℃-70℃. S5. Drying: Put the workpiece into the hot air dryer and dry it with hot air. S6. Nitriding: It is carried out in a JT-25 gas nitriding furnace, using ammonia and ethanol as nitriding agents and MgCl2 as a catalyst. S7, Heating Dust Treatment: Heat and apply to the workpiece. S8. Cooling.

2. The anti-corrosion process for a screw vacuum pump screw according to claim 1, characterized in that: In S3, the cathode is electrolyzed for 1 to 2 minutes, and the anode is electrolyzed for 10 to 20 seconds.

3. The anti-corrosion process for a screw vacuum pump screw according to claim 1, characterized in that: The process of S6 includes: (1) Place the workpiece in a gas nitriding furnace and seal the gas nitriding furnace. (2) The temperature in the gas nitriding furnace is set at 570°C-600°C and heated for 4 hours. (3) After the treatment is completed, turn off the ethanol and continue to pass ammonia at 100L / h to maintain a positive pressure of 400-500KPa in the furnace. (4) After infiltration, air cool the mixture after it is taken out of the furnace.

4. The anti-corrosion process for a screw vacuum pump screw according to claim 1, characterized in that: The heating and applying step in S7 includes: (1) First heating: Place the workpiece in a hot oven and heat it at 300°C for more than 40 minutes. (2) First powder coating: flame temperature: 1800°C, flame speed: 1000m / s, powder feeding speed: 100-150g / min, powder feeding gas flow: 600-800L / h (3) Secondary heating: Place the workpiece in a hot oven and heat it at 500°C for more than 40 minutes (4) Secondary powder coating: flame temperature: 2000°C, flame speed: 1500m / s.

5. The anti-corrosion process for a screw of a screw vacuum pump according to claim 3, characterized in that: The amount of ammonia passed in (2) is 500 L / h, and the amount of anhydrous ethanol is 50 L / min.

6. The anti-corrosion process for a screw vacuum pump screw according to claim 4, characterized in that: In the step (4), the powder feeding speed is 80-100 g / min, and the powder feeding gas flow rate is 400-600 L / h.